Association between occupational physical activity and myocardial infarction: a prospective cohort study. Issue 10 (3rd October 2016) - Johnsen, Anna M; Alfredsson, Lars; Knutsson, Anders; Westerholm, Peter J M; Fransson, Eleonor I
Abstract : Objective: Recommendations regarding physical activity typically include both leisure time and occupational physical activity. However, the results from previous studies on occupational physical activity and the association with myocardial infarction have been inconsistent. The aim of this study was to investigate if occupational physical activity is associated with the risk of myocardial infarction. Design: Prospective cohort study. Participants: Data from the Swedish Work, Lipids and Fibrinogen (WOLF) study was used, comprising 9961 employees (6849 men, 3112 women, mean age 42.7 years) having no history of myocardial infarction. The participants were categorised into 3 groups according to their level of occupational physical activity. Outcome: Data regarding incident myocardial infarction were obtained from the Swedish National Patient Register and the Cause of Death Register. Cox proportional hazard regression was used for estimation of HRs for different levels of occupational physical activity in relation to the risk of myocardial infarction. Results: During a mean follow-up of 13.1 years, 249 cases of incident myocardial infarction were identified. In analyses adjusted for age, sex and socioeconomic status, participants standing and walking more than 50% of their working day had an HR of 1.13 (95% CI 0.83 to 1.54), compared with participants seated more than 50% of their working day. The corresponding HR for participants whose work included lifting or carrying was 0.86 (95% CI 0.59 to 1.24). Further adjustment did not alter the results. Stratified analyses resulted in a significantly decreased risk for young people whose work included lifting or carrying, HR 0.37 (95% CI 0.17 to 0.84), compared with younger persons who sat most of their working day. Conclusions: No significant association between occupational physical activity and the risk of myocardial infarction was observed in the total group of employees in this study. Based on the results from this study, occupational physical activity in general does not seem to be enough for reducing the risk of myocardial infarction.